2014
DOI: 10.18632/oncotarget.3120
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1,2 inhibition impairs EZH2- and BBAP- mediated DNA repair to overcome chemoresistance in EZH2 gain-of-function mutant diffuse large B-cell lymphoma

Abstract: Gain-of-function mutations in the catalytic site of EZH2 (Enhancer of Zeste Homologue 2), is observed in about 22% of diffuse large B-cell lymphoma (DLBCL) cases. Here we show that selective inhibition of histone deacetylase 1,2 (HDAC1,2) activity using a small molecule inhibitor causes cytotoxic or cytostatic effects in EZH2 gain-of-function mutant (EZH2GOF) DLBCL cells. Our results show that blocking the activity of HDAC1,2 increases global H3K27ac without causing a concomitant global decrease in H3K27me3 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 62 publications
8
42
0
Order By: Relevance
“…Although there is often high responsiveness at first, the majority of patients eventually progress to platinum-resistant disease. HDAC1 expression is associated with drug resistance in several cancers [10,11,13,33,34]. Cacan et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is often high responsiveness at first, the majority of patients eventually progress to platinum-resistant disease. HDAC1 expression is associated with drug resistance in several cancers [10,11,13,33,34]. Cacan et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…26 Previous studies showed that hyperacetylation induced by sodium butyrate stimulates nucleotide excision repair in UVirradiated cells. 8,10,[47][48][49][50] The stimulation of DNA repair was shown to be associated with alterations in chromatin structure making damaged sites in DNA more accessible to repair enzymes. Moreover, impaired chromatin relaxation observed in the presence of the HAT inhibitor garcinol, suppressed the NHEJ pathway in DSBs repair 36 .…”
Section: Discussionmentioning
confidence: 99%
“…HDAC1 and 2, which are exclusively found in the nucleus of cells as they do not contain a nuclear export signal (108,109), deacetylate acetylated lysine 56 of histone 3 (H3K56Ac) (110,111) and acetylated lysine 16 of histone 4 (H4K16Ac) (110) (Figure 1C). In addition, inhibition of HDAC1 and 2 increases acetylation of histone 4 at lysine 91 (H4K91Ac) (112) (Figure 1C). Decreased H3K56Ac, H4K16Ac and H4K91Ac deacetylation due to the lack of or inhibition of, HDAC1 and 2 were paralleled by decreased survival of cells upon the induction of DSBs (110,112), and HDAC1 and 2 could, therefore, promote DSB repair by removing histone marks at DSBs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inhibition of HDAC1 and 2 increases acetylation of histone 4 at lysine 91 (H4K91Ac) (112) (Figure 1C). Decreased H3K56Ac, H4K16Ac and H4K91Ac deacetylation due to the lack of or inhibition of, HDAC1 and 2 were paralleled by decreased survival of cells upon the induction of DSBs (110,112), and HDAC1 and 2 could, therefore, promote DSB repair by removing histone marks at DSBs. The PcG polycomb repressive complex 1 (PRC1) contributes to the ubiquitination of histone H2A following the induction of DSBs (103,113115).…”
Section: Introductionmentioning
confidence: 99%